Esthetic and Clinical Performance of Implant-Supported All-Ceramic Crowns Made with Prefabricated or CAD/CAM Zirconia Abutments: A Randomized, Multicenter Clinical Trial. (February 2017) - Wittneben, J.G.; Gavric, J.; Belser, U.C.; Bornstein, M.M.; Joda, T.; Chappuis, V.; Sailer, I.; Brägger, U.
Patients' esthetic expectations are increasing, and the options of the prosthetic pathways are currently evolving. The objective of this randomized multicenter clinical trial was to assess and compare the esthetic outcome and clinical performance of anterior maxillary all-ceramic implant crowns (ICs) based either on prefabricated zirconia abutments veneered with pressed ceramics or on CAD/CAM zirconia abutments veneered with hand buildup technique. The null hypothesis was that there is no statistically significant difference between the 2 groups. Forty implants were inserted in sites 14 to 24 (FDI) in 40 patients in 2 centers, the Universities of Bern and Geneva, Switzerland. After final impression, 20 patients were randomized into group A, restored with a 1-piece screw-retained single crown made of a prefabricated zirconia abutment with pressed ceramic as the veneering material using the cut-back technique, or group B using an individualized CAD/CAM zirconia abutment (CARES abutment; Institut Straumann AG) with a hand buildup technique. At baseline, 6 mo, and 1 y clinical, esthetic and radiographic parameters were assessed. Group A exhibited 1 dropout patient and 1 failure, resulting in a survival rate of 94.7% after 1 y, in comparison to 100% for group B. No other complications occurred. Clinical parameters presented stable and healthy peri-implant soft tissues. Overall, no or only minimal crestal bone changes were observed with a mean DIB (distance from the implant shoulder to the first bone-to-implant contact) of −0.15 mm (group A) and 0.12 mm (group B) at 1 y. There were no significant differences at baseline, 6 mo, and 1 y for DIB values between the 2 groups. Pink esthetic score (PES) and white esthetic score (WES) values at all 3 examinations indicated stability over time for both groups and pleasing esthetic outcomes. Both implant-supported prosthetic pathways represent a valuable treatment option for the restoration of single ICs in the anterior maxilla (ClinicalTrials.gov NCT02905838).